The Surgical Strategy for Progressive Dilatation of Aortic Root and Aortic Regurgitation After Repaired Tetralogy of Fallot: A Case Report - Zhang, Shuaipeng; Liu, Haiyuan; Wang, Xiangyu; Huang, Shaojun; Zhang, Chengxin (Frontiers in Cardiovascular Medicine, 2022)
It has been found that postoperative progressive dilatation of aortic root is not rare for adult patients with repaired Tetralogy of Fallot, which leads to severe aortic regurgitation or even fatal dissection. Therefore, clinically, surgical treatment for both regurgitated aortic valve and dilated root is needed based on preoperative assessments and individual treatment strategies.